MENELUSURI MAKNA DRAMA FAUST I KARYA J. W. VON GOETHE - Isti Haryati (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe the meanings of the signs in the Faust I drama script in terms of the relationship between human beings and the Satan. Its position in German literature, structure, and texture were analyzed. It was analyzed through two reading stages, namely heuristics and hermeneutics; then, the matrix, variance, hypogram, and intertextual relationship were analyzed. In Faust I, Goethe wishes to emphasize the existence of human beings who establish relationship with the Satan because of their desireto acquire scientific knowledge. The strong desire is constrained by limitation, making them take a wrong path by establishing relationship with the Satan.